Volatile organic compounds (VOCs) as a rapid means for assessing the source of coprolites - Wanyue Zhao; Helen L. Whelton; John C. Blong; Lisa-Marie Shillito; Dennis L. Jenkins; Ian D. Bull (iScience, 2023)
Summary: The odor of rehydrated coprolites can be used as an informal means of fecal identification. To date, the analysis of volatiles emitted by coprolites from different sources has not been attempted, and the possibility of utilizing volatile organic compounds (VOCs) as fecal biomarkers unexplored. VOCs released by coprolites from the Paisley Caves, were analyzed using solid-phase microextraction (SPME), to assess the variance of results from different coprolites (carnivores, herbivores, or humans). Coprolites from carnivores can be clearly distinguished from those produced by herbivores and humans; these latter two are separated to a lesser degree. Eight discriminatory compounds differentiated between the coprolite sources, and their identities were verified using reference standards. Coprolites and their associated sediments could not be differentiated between using this method, suggesting leaching of VOCs into the burial matrix. This work provides an alternative, more rapid way to assess coprolite origin.